Intensive blood-pressure lowering in patients with acute cerebral hemorrhage - Qureshi, Adnan; Steiner, Thorsten (The New England journal of medicine, 2016)
In this randomized trial involving patients with intracerebral hemorrhage, intensive reduction in systolic blood pressure to a target of 110 to 139 mm Hg did not result in a lower rate of death or disability than standard reduction to a target of 140 to 179 mm Hg.